#TITLE_ALTERNATIVE# - SALLE KARURUNG (NIM 10202068), HARIYANTO
Seismoelectric is a geophysical method that uses mechanic energy conversion phenomena and becomes electric energy or electromagnetic through a specific conversion mechanism (i.e. electrokinetic effect). A seismoelectric measurement had been done using single channel (a dipole antenna) and obtained signal records in the traces. By using block subtraction’s method, these recorded signals were processed to suppress the noise. In this final project used some signal processing tools as Microsoft Excel and MATLAB Signal Processing Toolbox. The physical parameters which were measured during data acquisition were amplitude and time. After processing, it can be obtained the relation between these parameters with the others i.e. porosity, permeability, and materials’ density in subsurface. These seismoelectric signals carried information about subsurface and useful to understand it, mainly about interface boundaries.